Digital technology diffusion A matter of capabilities, incentives or both? - Andrews, Dan (OECD Economics Department Working Papers, 2018)
Insufficient diffusion of new technologies has been quoted as one possible reason for weak productivity performance over the past two decades (Andrews et al., 2016). This paper uses a novel data set of digital technology usage covering 25 industries in 25 European countries over the 2010-16 period to explore the drivers of digital adoption across two broad sets of digital technologies by firms, cloud computing and back or front office integration. The focus is on structural and policy factors affecting firms' capabilities and incentives to adopt -- including the availability of enabling infrastructures (such as high-speed broadband internet), managerial quality and workers skills, and product, labour and financial market settings. We identify the effects of structural and policy factors based on the difference-in-difference approach pioneered by Rajan and Zingales (1998) and show that a number of these factors are statistically and economically significant for technology adoption. Specifically, we find strong support for the hypothesis that low managerial quality, lack of ICT skills and poor matching of workers to jobs curb digital technology adoption and hence the rate of diffusion. Similarly our evidence suggests that policies affecting market incentives are important for adoption, especially those relevant for market access, competition and efficient reallocation of labour and capital. Finally, we show that there are important complementarities between the two sets of factors, with market incentives reinforcing the positive effects of enhancements in firm capabilities on adoption of digital technologies